Case report of osteoarticular tuberculosis: Diagnostic difficulty and probable primary infection - Valladares Díaz, Carlos Diego (2017)
We report the case of a 36-year-old male from Ancash, Peru, who attended to a local hospital due to articular pain in the right knee for three years. Diagnosis was not reached in that hospital and months later he visited Hospital Nacional Dos de Mayo in the capital city, where evaluation and treatment for osteoarticular tuberculosis was started after finding a granulomatous inflammatory process in a bone biopsy. Such diagnosis was confirmed later by a positive culture of synovial fluid after a more than 45-month disease period. The atypical presentation, absence of a primary site and diagnostic difficulty of the disease in a country where tuberculosis is still endemic encouraged the publication of this case report.